2017
DOI: 10.1038/s41467-017-02311-8
|View full text |Cite
|
Sign up to set email alerts
|

PCH1 and PCHL promote photomorphogenesis in plants by controlling phytochrome B dark reversion

Abstract: Phytochrome B (phyB) is the primary red light photoreceptor in plants, and regulates both growth and development. The relative levels of phyB in the active state are determined by the light conditions, such as direct sunlight or shade, but are also affected by light-independent dark reversion. Dark reversion is a temperature-dependent thermal relaxation process, by which phyB reverts from the active to the inactive state. Here, we show that the homologous phyB-binding proteins PCH1 and PCHL suppress phyB dark … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 38 publications
2
83
0
Order By: Relevance
“…The rate of dark reversion (Enderle et al, ; Kim et al, ; Smith et al, ) and the formation of phyB NBs (Bauer et al, ) are two features of the phyB system that can be affected by biochemical interactions and developmental context. Because the parameters that are most influential for D 2 estimation ( k r1 , k 31 , and k 41 ) are actually associated to dark reversion and phyB NB dynamics, we investigated the impacts of k r1 , k 31 , and k 41 on the estimation of biological outputs under the shade‐avoidance conditions (i.e., in light‐grown seedlings).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of dark reversion (Enderle et al, ; Kim et al, ; Smith et al, ) and the formation of phyB NBs (Bauer et al, ) are two features of the phyB system that can be affected by biochemical interactions and developmental context. Because the parameters that are most influential for D 2 estimation ( k r1 , k 31 , and k 41 ) are actually associated to dark reversion and phyB NB dynamics, we investigated the impacts of k r1 , k 31 , and k 41 on the estimation of biological outputs under the shade‐avoidance conditions (i.e., in light‐grown seedlings).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the cellular context can affect P fr to P r thermal reversion. This could occur via changes in the phosphorylation status of the phyB molecule (Medzihradszky et al, 2013) and changes in the status of phyB interacting partners such as the transcriptional regulators called phytochrome interacting factors (Smith et al, 2017) or the photoperiodic control of hypocotyl 1 protein (Enderle et al, 2017), all of which reduce the rate of thermal reversion. Actually, phyB synthesized in vitro is much less stable than phyB in vivo (Legris et al, 2016), and it has been proposed that phyB is protected from thermal reversion within NBs (Klose et al, 2015;Rausenberger et al, 2010;Van Buskirk et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New Phytologist OF HYPOCOTYL 1 (PCH1) and its homolog PCHL (PCH1like), which accumulate in light and colocalize with phyB in PBs, were shown to inhibit phyB thermal reversion upon phyB binding (Huang et al, 2016;Enderle et al, 2017). Furthermore, a very recent study demonstrated that PCH1 stabilizes phyB Pfr in vitro and that PCH1 is an essential structural component of phyB PBs (Huang et al, 2019).…”
Section: Researchmentioning
confidence: 99%
“…This could be due to different phyB binding partners or slightly different active phyB forms among 70,72 . Three phyB-interacting proteins have been reported to stabilize the Pfr form by suppressing its dark reversion, they are ARABIDOPSIS RESPONSE REGULATOR 4 (ARR4) 73 , PHOTOPERIODIC CONTROL OF HYPOCOTYL 1 (PCH1) [50][51][52] , and PCH1-LIKE (PCHL) 52 . In particular, PCH1 and PCHL facilitate the PB localization of phyB [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%